THE CLOSED CIRCLE "DEATH–LIFE–DEATH": CINEMA POETICS OF THE COLLECTION OF VASILY STEFANIK "DOROHA" - Virchenko, T. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
The article is devoted to the study of film poetics of Vasyl Stefanyk's collection "The Road". The purpose of the investigation is to give an answer to the problematic question: is the artist consistent in the use of film poetic means. Stefanikologists consistently state the visuality of the writer's short stories, but these statements are devoid of careful textual analysis. The author uses a proven method that involves paying attention to the artistic space, the inner world of the characters, colors, sounds and artistic details. The main research attention will be paid to the works «The Road», «Skin», «Palium», «Funeral», «Dream», «Ozymina», «Such a Man». This constitutes the historical and literary novelty of the work. As a result, the coloristics of plans, the semantics of artistic details, the images presented in close-up, the dynamics of events in the frame were analyzed; it was found that only semantically meaningful images are presented in close-up, the colors of successively arranged frames match, and the used sounds add harmony to the frames. In the short stories, there is an alternation of general and close-up shots, the last and first short stories create integrity thanks to the use of the visual image of the road.